Nanomaterials-based biosensing strategies for biomarkers diagnosis, a review - Heydari-Bafrooei, Esmaeil; Ensafi, Ali A. (Biosensors and bioelectronics. X, 2023)
The accurate detection of potential biomarkers in body fluids is a vital step in the early detection of specific diseases, monitoring of effective treatment, and development of modern drugs. In recent years, the superiority of biosensors in biomarkers detection has been highlighted because of their inherent advantages such as cost-effectiveness, much friendlier preparation and determination steps, portability, and fast response time. With the introduction of nanomaterials into biosensing fields, the analytical characteristics of biosensors have improved dramatically. The primary reasons for using nanomaterials in biosensors are signal amplification and sensitivity enhancement. Other biosensor features, such as selectivity, resolution, response time, linearity, repeatability, robustness, biocompatibility, and stability can also be improved by functionalized nanomaterials. Increasing the effective surface area, efficient immobilization of biomolecules, catalysis of the electrochemical and optical events and lowing the activation energy, accelerating the electron transfer, separation of the biomolecule's conjugates and pre-concentration of the analyte, and labeling of the bioreceptors can be considered as the most significant reasons for using of nanomaterials in biosensors. This review provides a comprehensive overview of nanomaterials in the amplification of characteristics of the biosensors and the results and importance of using nanomaterials. New strategies for enhancing the analytical features of the biosensing systems using nanomaterials are also analyzed in detail. Ultimately, current challenges and prospects were discussed as well. [Display omitted] •The non-invasive determination of the biomarkers in biological fluids is very important in the early detection of diseases.•This review highlighted the progress and application of nanomaterials for biomarkers biosensing.•The role of nanomaterials in enhancing biosensor characteristics was discussed.•Current challenges and future perspectives were discussed.